2018
DOI: 10.1536/ihj.17-672
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Influence and Predictors of Pacing-Induced Mechanical Asynchrony in Patients with Normal Cardiac Function with Ventricular Lead Placed in Non-Apical Position

Abstract: Right ventricular apical (RVA) pacing often causes left ventricular (LV) mechanical asynchrony, which is enhanced by impaired cardiac contraction and intrinsic conduction abnormality. However, data on patients with normal cardiac function and under RV non-apical (non-RVA) pacing are limited. We retrospectively investigated 97 consecutive patients with normal ejection fraction who received pacemaker implantation for atrioventricular block with the ventricular lead placed in a non-RVA position. We defined mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…A trial fibrillation (AF) is one of the most common cardiac arrhythmias in clinical practice, 1) and an epidemiological survey showed that AF significantly increases the incidence of stroke and mortality. 2) The current therapy in patients with drug-refractory AF is surgical operation or cardiac radiofrequency ablation, 3) but the long-term outcome of ablation for even the earliest stage of AF is disappointing.…”
mentioning
confidence: 99%
“…A trial fibrillation (AF) is one of the most common cardiac arrhythmias in clinical practice, 1) and an epidemiological survey showed that AF significantly increases the incidence of stroke and mortality. 2) The current therapy in patients with drug-refractory AF is surgical operation or cardiac radiofrequency ablation, 3) but the long-term outcome of ablation for even the earliest stage of AF is disappointing.…”
mentioning
confidence: 99%